Attempted Depletion of Passenger Leukocytes by Irradiation in Pigs - Hao-Chih Tai; Xiaocheng Zhu; Yih Jyh Lin; Hidetaka Hara; Mohamed Ezzelarab; Michael Epperley; Mubina A. Quader; David K. C. Cooper (Journal of Transplantation)
Allograft/xenograft rejection is associated with “passenger leukocyte” migration from the organ into recipient lymph nodes. In Study 1, we attempted to deplete leukocytes from potential kidney “donor” pigs, using two regimens of total body irradiation. A dose of 700 cGy was administered, followed by either 800 cGy (“low-dose”) or 1,300 cGy (“high dose”) with the kidneys shielded. Neither regimen was entirely successful in depleting all leukocytes, although remaining T and 8 cell numbers were negligible. Study 2 was aimed at providing an indication of whether near-complete depletion of leukocytes had any major impact on kidney allograft survival. In non-immunosuppressed recipient pigs, survival of a kidney from a donor that received high-dose irradiation was compared with that of a kidney taken from a non-irradiated donor. Kidney graft survival was 9 and 7 days, respectively, suggesting that depletion had little impact on graft survival. The lack of effect may have been related to (i) inadequate depletion of passenger leukocytes, thus not preventing a direct T cell response, (ii) the presence of dead or dying leukocytes (antigens), thus not preventing an indirect T cell response, or (iii) constitutive expression of MHC class II and B7 molecules on the porcine vascular endothelium, activating recipient T cells.